BANGTAN SEONYEONDAN (BTS) MUSIC VIDEO “IDOL” AS A REPRESENTATION OF KOREAN POP CULTURE - Hani Gustiya Ningsih; Indra Tjahyadi (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
This research aims to find out about Korean traditional culture that is becoming popular culture in Korea today in BTS